2015
DOI: 10.4094/chnr.2015.21.1.74
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Meaning in Life in Adolescents with Leukemia.

Abstract: The purpose of this study was to identify predictors of spiritual well-being and meaning in life for adolescents with leukemia. Methods: Participants were 102 adolescents (11-21 years) recruited at C university hospital from June to August in 2014. The eligible participants were diagnosed with leukemia and are on follow-up care at the outpatient clinic. Participants were assessed for spiritual well-being, meaning in life, self-esteem, and social support. Results: Levels of spiritual well-being and meaning in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…95 One study suggested that patients may find meaning in cancer by: attempting to define the disease, viewing cancer as a ‘‘divine test’’, or as a catalyst for positive self-reconstruction. 96 Intrinsic factors, such as self-esteem, 44 religious faith, 97 spiritual well-being, 98 and positive coping strategies, 99 correlated with meaning discovery. Interventions that may improve meaning discovery include increasing social support, 98 legacy making through story or art, 100 increased benevolence toward others, 64 and certain meaning-centered programs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…95 One study suggested that patients may find meaning in cancer by: attempting to define the disease, viewing cancer as a ‘‘divine test’’, or as a catalyst for positive self-reconstruction. 96 Intrinsic factors, such as self-esteem, 44 religious faith, 97 spiritual well-being, 98 and positive coping strategies, 99 correlated with meaning discovery. Interventions that may improve meaning discovery include increasing social support, 98 legacy making through story or art, 100 increased benevolence toward others, 64 and certain meaning-centered programs.…”
Section: Resultsmentioning
confidence: 99%
“… 96 Intrinsic factors, such as self-esteem, 44 religious faith, 97 spiritual well-being, 98 and positive coping strategies, 99 correlated with meaning discovery. Interventions that may improve meaning discovery include increasing social support, 98 legacy making through story or art, 100 increased benevolence toward others, 64 and certain meaning-centered programs. 101 Finally, there is evidence that fulfilling employment, meeting education goals, 102 and accomplishing tasks 103 may improve meaning discovery in patients with cancer.…”
Section: Resultsmentioning
confidence: 99%
“…In another study by Oh, spiritual intervention was reported to have a significant, moderate impact on the spiritual well-being, life perception, and depression of patients (22). In this regard, Hong (2015) denoted social support and self-esteem to remarkably influence 68% of the studied patients, emphasizing on the importance of social support in cancer patients (23). Results of several studies have confirmed a positive correlation between the spiritual well-being and overall health of different patients (24).…”
Section: Discussionmentioning
confidence: 98%